UNDERSTANDING THE FEELINGS AND MOTIVATION OF AFGHAN STUDENTS’ REGARDING STUDYING AT CHINESE UNIVERSITIES - Bahir, Hizbullah Bahir; ., Huanghe (American International Journal of Social Science Research, 2021)
Making a decision to study in foreign countries is considered one of the most difficult tasks. However, it is one of the most essential and valuable attempts for the students because in foreign countries the quality of lessons are high and they can make huge social relations with learners. Also, China accepts students from all over the world. This study examined the feelings, and motivations of Afghan students; the data was collected through google form and constructed interview which 99 students were the participants. A mixed approach was used for this study. Moreover, the interview was done with those learners who have been completed their higher education in the country of China and the data was analyzed through SPSS 26 version. The findings asserted that learning of students in China is very beneficial as well with the relations of other foreign countries who study in China. Furthermore, the findings indicated more that learners have noticeable achievements in the parts of the culture of China, new technology; learning of Chinese language. Additionally, in China living allowance, medical services, well-equipped dormitories and the services of seeing historical places are free of charge for the better life of students. JEL Classification Codes: A19, B10, B25, C10, C53.